2020
DOI: 10.1002/col.22486
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and reflectance properties of viscose/polyester blend fabric printed by vat/disperse dyes in visible/near‐infrared region

Abstract: In this study, a viscose/polyester fabric was printed by disperse and vat dyes to match the reflectance characteristics of the NATO black and green hues with forest environment in the visible/near‐infrared (Vis‐NIR) reflection spectrum. The black and activated carbon nanoparticles were also added to the printing paste to match the reflectance of hues. Color components and Vis‐NIR reflective behavior of printed fabrics were measured by reflection spectrophotometer. The rubbing, washing and light fastness, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The work of many researchers demonstrates the importance of wearer comfort, resistance to laundering, and maintaining the functionality of the garment over time [ 14 , 16 , 23 , 31 , 34 , 39 , 40 , 44 ]. There are benefits in avoiding the need for embedded electronics as this adds complexity in terms of washing and powering of devices, especially since energy harvesting capabilities are not ready for use in textile systems yet.…”
Section: Discussion and Path Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of many researchers demonstrates the importance of wearer comfort, resistance to laundering, and maintaining the functionality of the garment over time [ 14 , 16 , 23 , 31 , 34 , 39 , 40 , 44 ]. There are benefits in avoiding the need for embedded electronics as this adds complexity in terms of washing and powering of devices, especially since energy harvesting capabilities are not ready for use in textile systems yet.…”
Section: Discussion and Path Forwardmentioning
confidence: 99%
“…Visible camouflage in military fabrics is generally achieved using colors and patterns that resemble the color, intensity, pattern, texture, and appearance of a soldier’s natural or artificial environment through dyeing or pigmentation techniques [ 2 , 21 ]. Dyed or pigmented fabrics’ CIE (Commission International de l’Eclairage) color parameters are measured using spectrophotometers, which identify colors based on its lightness, red/green and yellow/blue values, and its reflectance properties [ 22 , 23 ]. Textiles also must be colored using NIR reflecting dyes or pigments to match the reflectance curves or “chlorophyll rise” of vegetation in the NIR range [ 2 , 21 ] (p. 444).…”
Section: Existing Technologies Applicable To Visible and Ir Camouflagementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that 300 mesh, 600 mesh, 1250 mesh, 2000 mesh, and 2500 mesh hollow ceramic beads could reduce the thermal conductivity of the coating, and the thermal conductivity of the coating with 600 mesh beads was the lowest. Some researchers 50 used TiO 2 nanoparticles as thermal insulation coatings for thermal infrared camouflage fabrics and applied them evenly and firmly on the fabrics at 90°C by low-temperature atomic layer deposition (ALD) technology. The experimental data showed that after 2000 ALD cycles, the infrared and thermal insulation rates increased from 67.6% and 28.5% to 86.7% and 63.9%, respectively (Figure 7(a)–(d)).…”
Section: Control Temperaturementioning
confidence: 99%
“…Also, it changes the number of color components in the printed fabrics. 18 Starting from these considerations, in the present study, forest green textile inks for screen printing were formulated according to the NATO and USA standards [19][20][21] by the experimental mixture design, a special type of the response surface methodology (RSM). The proposed textile ink aimed at the reproduction of NATO green, which is specific to camouflage materials used for the forest vegetation of the temperate climate and implemented for both uniforms and military technique in NATO armies.…”
mentioning
confidence: 99%